Experimental Validation of Sustainable Aviation Fuel (SAF) Blending and Testing Methodologies for Small Turbofan Engine - Alex Ayedun Avwunuketa; Michael Quaicoe; Francis Ayomide Adedeji (ABUAD Journal of Engineering Research and Development, 2025)
Much research has been undertaken on the sustainable aviation fuels as the alternative to jet A-1 fuels due to magnitude demands of having carbon-free alternative fuel in the aviation industry. This study gives information on the combustion dynamics and emission performance of synthetic fuel blends of a small PTD 500 turbofan engine using a kinetically shaped reactivity model that is dependent on chemical kinetics and thermodynamics. Several blends of fuels containing different volumes of SAF content were created and tested on their conformance with ASTM D7566 and ASTM D4054 requirements. The experimental test of the engine measured thrust, fuel consumption and emissions over a range of operating conditions, reactivity model included activation energy and combustion kinetics to measure the dependence of fuel mass flow on exhaust gas forming Combustion behaviours was correlated to thrust output and CO and  emissions by use of α 1 reactivity coefficient. In terms of the Take-off operation, the thrust contribution of engines ranged between 80%-90% but in idle operation, recorded 10%-15.As evident in the results, addition of SAF has insignificant impact on engine thrust gain, with significant impacts on combustion paths and routes related to the incomplete combustion formation. This was proved empirically as there was no difference in the consistency of the fuel blends and these differences in combustion chemistry were related to the change in the composition and calorific value of the hydrocarbons. The present research has established the compatibility of SAF with the existing engine systems and also the need to have a detailed kinetic model to optimize the use of fuel and reduce its environmental effects. The reactivity model is expected to be extended in future to include long-term engine operating conditions under typical SAF applications, which can be used to support the propulsion aviation sector transition to green propulsion.